How do individual-level factors influence the adoption of low-carbon technology? Proposing and validating the bioeconomy technology acceptance model in the context of Africa - Oguntuase, Oluwaseun J.; Adu, Oluwatosin B.; Obayori, Oluwafemi S. (Frontiers in Sustainability, 2023)
The bioeconomy seeks to efficiently transform biomaterials into value added products to achieve circularity. A circular bioeconomy is a circular carbon economy based on bio-based resources.There is a dearth of information in the literature about how psychological factors affect public acceptance of the bioeconomy, especially in Africa where adoption of bioeconomy is scant. Addressing this gap, this study characterized bioeconomy as a low-carbon bio-based technological innovation to combat climate change and developed the Bioeconomy Technology Acceptance Model (BTAM) to explain the effects of individual-level factors on public acceptance of bioeconomy and investigated it in a survey (N=465) using questionnaires that was carried out in Lagos, Nigeria in 2022. The respondents were chosen by proportional stratified random sampling, and descriptive statistics, Pearson's correlation coefficient, and structural equation modeling were used to analyze the data obtained. The strong influence of perceived usefulness from bioeconomy and intention to accept bioeconomy in BTAM suggests that the Technology Acceptance Model (TAM) is suitable for predicting public acceptance of bioeconomy. Considering the strong influence of belief about climate change on perceived usefulness of bioeconomy and intention to accept it in this study, it is imperative to promote climate change education among Africans to accelerate acceptance of bioeconomy on the continent. The identified psychological factors provide reference for scholars, policymakers and manufacturers to effectively develop individual-oriented intervention strategies and promotion schemes to enhance acceptance of bioeconomy in Africa in particular and other climes where there is not yet widespread acceptance of circular bioeconomy.